ROOT CAUSE ANALYSIS OF SPALL AND CRACK ON THE COACH WHEEL USED BY PT. KERETA API (PERSERO) - DELANIS SEMBIRING (NIM : 231 08 013); Pembimbing : Prof. Dr. Ir. IGN. Wiratmaja Puja; Dr. Ir, HARSA
One of the main means of transportation for the land route is a train. The railway operations may be disrupted in the event of damage or failure of the train components. One of the train components that often damaged are the wheels. From the data, it was found two types of dominant damage mode, spall and crack defects on the surface of the wheel. Spall on the surface of the wheel results an excessive vibration, thereby reducing passenger comfort when using the train. Root cause analysis of spall and crack on the coach wheel has been performed to determine the wheel failure mode that happens and also to explore the source of the wheels damage so the proper care and prevention can be taken for the case of subsequent damage. This study was conducted by collecting data of the spalls and cracks failure of wheels in the field and laboratory test. To complete the analysis, the braking simulation by analytic methods and also investigate the static wheel loading with elements modeling using ANSYS Multiphysics software. The results of the analysis explains that the wheel failure mode is overlap ellipse-shaped defects with the same pattern direction, developed into a spall with crack and in certain conditions can develop into flat wheel. Static modeling of the wheel showed the contact stress that was occur is 904,551 MPa, below the wheel strength (about 1000 MPa). Through the observation of micro structure during the test showed that there had been changes in the micro structure of the wheel into martensite due to excessive temperature, mean temperature of the wheel has been reached 800oC. Martensite structure is formed by the heat that comes when the wheel friction with composite brake blocks and the wheels slide on the rail, followed by rapid cooling that occurred repeatedly. According to the graph resulting from braking simulation, skidding was happen when the friction coefficient of the brake block is 0,24 and static friction coefficient between wheel and rail is 0,15. Martensitic structure of the wheel surface is brittle and easily chip-off, and vulnerable to fracture because of the low ductility. Spall defects that occur in the wheels are always accompanied by a subtle crack at the bottom. Cracks that occur at the edge of the wheel were caused by the heating effect experienced by wheel.